2005
DOI: 10.1002/cne.20481
|View full text |Cite
|
Sign up to set email alerts
|

Exuberant thalamocortical axon arborization in cortex-specific NMDAR1 knockout mice

Abstract: Development of whisker-specific neural patterns in the rodent somatosensory system requires NMDA receptor (NMDAR)-mediated activity. In cortex-specific NR1 knockout (CxNR1KO) mice, while thalamocortical afferents (TCAs) develop rudimentary whisker-specific patterns in the primary somatosensory (barrel) cortex, layer IV cells do not develop barrels or orient their dendrites towards TCAs. To determine the role of postsynaptic NMDARs in presynaptic afferent development and patterning in the barrel cortex, we exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
99
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(110 citation statements)
references
References 61 publications
11
99
0
Order By: Relevance
“…This is based principally on the observations that barrel centers are discernible cytoarchitecturally earlier than septa (Rice and Van der Loos, 1977) and that VPM TCAs are present within infragranular layers at birth and rapidly (within ~1–2 days) form whisker-related clusters (Wise and Jones, 1978; Erzurumlu and Jhaveri, 1990; Senft and Woolsey, 1991; Agmon et al, 1993; Schlaggar and O’Leary, 1994; Catalano et al, 1996; Rebsam et al, 2002). Our data demonstrate that POm TCAs are also well-represented within infragranular layers by birth in both rats and mice, in agreement with a previous study of POm TCAs in developing rats (Galazo et al, 2007), and exhibit single-fiber morphology and a laminar innervation pattern very similar to those reported for VPM axons (Catalano et al, 1996; Rebsam et al, 2002; Lee et al, 2005). Thus, at birth, both sets of TCAs from POm and VPM nuclei are present and extend equally into the barrel cortex, which dispels the notion that there is a major temporal disparity in the arrival and positioning of the two sets of axons at the beginning of postnatal life.…”
Section: Discussionsupporting
confidence: 92%
“…This is based principally on the observations that barrel centers are discernible cytoarchitecturally earlier than septa (Rice and Van der Loos, 1977) and that VPM TCAs are present within infragranular layers at birth and rapidly (within ~1–2 days) form whisker-related clusters (Wise and Jones, 1978; Erzurumlu and Jhaveri, 1990; Senft and Woolsey, 1991; Agmon et al, 1993; Schlaggar and O’Leary, 1994; Catalano et al, 1996; Rebsam et al, 2002). Our data demonstrate that POm TCAs are also well-represented within infragranular layers by birth in both rats and mice, in agreement with a previous study of POm TCAs in developing rats (Galazo et al, 2007), and exhibit single-fiber morphology and a laminar innervation pattern very similar to those reported for VPM axons (Catalano et al, 1996; Rebsam et al, 2002; Lee et al, 2005). Thus, at birth, both sets of TCAs from POm and VPM nuclei are present and extend equally into the barrel cortex, which dispels the notion that there is a major temporal disparity in the arrival and positioning of the two sets of axons at the beginning of postnatal life.…”
Section: Discussionsupporting
confidence: 92%
“…NMDAR loss in the cortical neurons of Emx-Cre mice was not analyzed for each layer specifically. In cortical NR1 KO animals with Emx-Cre, rudimentary patches of barrels are formed, which is because of a lack of selective arborization of thalamocortical axons in layer 4 (32,34). However, in Nex-Cre-induced NR1 nulls, barrels are completely absent (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study in which monocular deprivation was combined with silencing cortical activity has further suggested that correlations between pre-and postsynaptic activity play a dominant role in segregation of axon arbors (12). In accordance with this view, molecular machinery in pre-and postsynaptic sites has also been shown to affect arbor formation of TC axons in the somatosensory cortex (13)(14)(15). However, the relative role of pre-and postsynaptic activity in TC axon branching remains unclear.…”
mentioning
confidence: 92%